Pure inorganic thixotropic gel with adjustable physical properties as well as preparation method and application of pure inorganic thixotropic gel

Ion assembly is carried out through inorganic one-dimensional nanorods of rare earth metal elements to form an adjustable pure inorganic thixotropic gel, which solves the problems of high cost of inorganic gel materials, complex preparation and limited strength adjustment, and achieves efficient and economical The possibility of gel physical properties and multiple applications.

CN119390026APending Publication Date: 2025-02-07ZHEJIANG UNIV OF TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411202485.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing inorganic gel materials have problems such as expensive materials, cumbersome preparation steps, requiring organic ligand modification, and small changes in strength.

Method used

An ion generation assembly is performed using inorganic one-dimensional nanorods of rare earth metal elements to form an adjustable pure inorganic thixotropic gel. This method does not require additional surface modification reagents, and adjusts the assembly structure of the nanorods by controlling the ion concentration, thereby adjusting the physical properties of the gel.

Benefits of technology

It realizes efficient adjustment of the physical properties of inorganic gels, with a strength change of more than 10,000 times, low material cost and simple operation, and is suitable for a variety of practical applications, such as wound recovery materials, drug carriers, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390026A_ABST
    Figure CN119390026A_ABST
Patent Text Reader

Abstract

The invention discloses thixotropic pure inorganic gel with adjustable physical properties as well as a preparation method and application of the thixotropic pure inorganic gel. The pure inorganic gel comprises loosely assembled nanorod assemblies and a solution for dispersing the loosely assembled nanorod assemblies, the nanorod assembly comprises an inorganic one-dimensional nanorod and anions capable of participating in the assembly of the inorganic one-dimensional nanorod; the inorganic one-dimensional nanorod at least contains rare earth metal elements. Compared with inorganic gel materials with other morphologies, the inorganic thixotropic gel disclosed by the invention can generate physical structure change through self-assembly of the inorganic one-dimensional nanorods, and has a relatively good physical property adjustment basis. And secondly, the inorganic one-dimensional nanorod can form an assembly through ions without additionally adding a surface modification reagent, the change of physical properties can be realized without replacing ligands, and the inorganic one-dimensional nanorod has extremely high advantages in various applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanomaterials and biomedicine, and in particular to a pure inorganic thixotropic gel with adjustable physical properties and a preparation method and application thereof. Background Art

[0002] At present, the physical properties of sol or gel are often adjusted by adding organic substances, thereby achieving changes in the physical properties of liquids through emulsification and other means, and finally applied to practical applications such as drug carriers, medical excipients, cosmetic materials, and sunscreen products. At the same time, products whose physical properties change during application, such as liquid bandages, injectable organic gels, and 3D printing consumables, almost all achieve state changes through organic substances to achieve the effect.

[0003] Nowadays, inorganic sols and gels with various functions are being developed. From the perspective of formation mechanism, inorganic hydrogels are classified into three types: those based on direct cross-linking, those based on modified ligands, and those based on electrostatic forces. Direct cross-linked inorganic hydrogels are composed of disordered one-dimensional inorganic material structures, which have poor flexibility and are not stimuli-responsive, so their scope of application is limited; modified ligand-based inorganic hydrogels are composed of zero-dimensional inorganic nanoparticles and expensive ligands, and their gel strength is also limited, so they generally do not meet the requirements for preparing hydrogels. Electrostatic force-based inorganic hydrogels have good gel properties, such as ligand-modified gold nanoparticles, graphene nanosheets, two-dimensional titanium oxide nanosheets, etc., and some materials also have certain temperature responsiveness. However, these materials are expensive, the preparation steps are cumbersome, and they require organic ligand modification, so they have not been widely used at this stage.

[0004] In addition, the current changes in the physical state of inorganic sols or gels can only change the strength by dozens of times, and cannot achieve a greater change. For example, titanium dioxide nanosheets can only change between a weaker gel and a stronger gel, which limits their application scenarios. Summary of the invention

[0005] The present invention aims to overcome the defects of inorganic gels in the prior art, such as expensive materials, complicated preparation steps, the need for organic ligand modification, and small strength variation, and provides a pure inorganic thixotropic gel with adjustable physical properties and a preparation method and application thereof to overcome the above-mentioned shortcomings.

[0006] To achieve the above-mentioned purpose, the present invention is implemented by the following technical solutions: In a first aspect, the present invention first provides a pure inorganic thixotropic gel with adjustable physical properties, wherein the adjustable physical properties at least include adjustable physical state, strength, and microscopic morphology, and the pure inorganic thixotropic gel comprises loosely assembled nanorod assemblies and a solution for dispersing the loosely assembled nanorod assemblies; The nanorod assembly comprises inorganic one-dimensional nanorods and anions that can participate in the assembly of the inorganic one-dimensional nanorods; and the inorganic one-dimensional nanorods at least comprise rare earth metal elements.

[0007] Preferably, the adjustable physical state includes converting the pure inorganic thixotropic gel into a pure inorganic stimuli-responsive sol or a pure inorganic typical gel.

[0008] Preferably, the adjustable intensity includes that at a shear frequency of 1 Hz, the intensity can be adjusted between 0.001 Pa and 1000000 Pa.

[0009] Preferably, the microscopic morphology is adjustable between dispersed nanorods and tightly assembled nanorod assemblies.

[0010] Preferably, the inorganic one-dimensional nanorods are phosphates of rare earth metal elements.

[0011] Preferably, the rare earth metal element is at least one of lanthanum, cerium, spectrium, promethium, samarium, europium and gadolinium.

[0012] Preferably, the concentration of inorganic one-dimensional nanorods in the pure inorganic sol is less than 200 mg / mL.

[0013] Preferably, the anions that can participate in the assembly of nanorods do not include chloride ions.

[0014] Preferably, the anions that can participate in the assembly of nanorods include one or more of nitrate ions, phosphate ions, hydroxide ions, phosphate ions, carbonate ions, molybdate ions, tungstate ions, titanate ions, sulfate ions, and bismuth ions.

[0015] Preferably, the anion concentration is 10 -15 -10M.

[0016] In a second aspect, the present invention also provides a method for preparing a pure inorganic thixotropic gel with adjustable physical properties, comprising the following steps: Under stirring conditions, a substance used to react with the salt of the rare earth metal element to form an inorganic one-dimensional nanorod and an inducer are added to a solution containing a salt of the rare earth metal element to form a uniform liquid, and at the same time, the inorganic one-dimensional nanorods are controlled to self-assemble to form a loosely assembled nanorod assembly, and the reaction obtains a pure inorganic thixotropic gel with adjustable physical properties as described in any one of the items.

[0017] Preferably, the salt of the rare earth metal element contains any one anion or a combination of multiple anions selected from the group consisting of nitrate ion, phosphate ion, hydroxide ion, phosphate ion, carbonate ion, molybdate ion, tungstate ion, titanate ion, sulfate ion and bismuth ion.

[0018] Preferably, the substance used to react with the salt of the rare earth metal element to form the inorganic one-dimensional nanorods is phosphoric acid.

[0019] Preferably, the inducer is an alkaline solution.

[0020] Preferably, the alkaline solution is any one or more combinations of ammonia water, sodium hydroxide and potassium hydroxide.

[0021] Preferably, the pH of the alkaline solution is greater than 9.

[0022] Preferably, the reaction temperature is 0-100° C., and the reaction can be terminated immediately after the precursor is added, or can be extended to several months to form nanorod assemblies with different morphologies.

[0023] In a third aspect, the present invention further provides a pure inorganic stimuli-responsive sol, comprising dispersed inorganic one-dimensional nanorods and a solution for dispersing the dispersed inorganic one-dimensional nanorods, wherein the inorganic one-dimensional nanorods contain at least a rare earth metal element.

[0024] Preferably, the anion concentration in the solution is less than 10 -15 M.

[0025] In a fourth aspect, the present invention also provides a method for converting the above-mentioned pure inorganic thixotropic gel with adjustable physical properties into a pure inorganic stimuli-responsive sol. The concentration of anions that can participate in the assembly of nanorods is removed or reduced in the pure inorganic thixotropic gel with adjustable physical properties until the loosely assembled nanorod assemblies in the pure inorganic thixotropic gel are transformed into dispersed inorganic one-dimensional nanorods, thereby obtaining the pure inorganic stimuli-responsive sol.

[0026] Preferably, the method for removing or reducing the concentration of anions that can participate in the assembly of nanorods comprises adding chemical solutions, centrifugation, dialysis or ultrafiltration.

[0027] Preferably, when the anions that can participate in the assembly of the nanorods are hydroxide ions or carbonate ions, the chemical solution is one or more of hydrochloric acid, nitric acid, boric acid, citric acid, and acetic acid.

[0028] Preferably, the dialysis time is greater than 1 hour, and the ultrafiltration time is greater than 1 minute; The external solution used for dialysis is one or more of hydrochloric acid, nitric acid, boric acid, citric acid, and acetic acid.

[0029] In a fifth aspect, the present invention also provides a method for converting the pure inorganic stimuli-responsive sol into a thixotropic gel, comprising adding anions that can participate in the assembly of inorganic one-dimensional nanorods into the pure inorganic stimuli-responsive sol until the dispersed inorganic one-dimensional nanorods are converted into loosely assembled nanorod assemblies.

[0030] In the sixth aspect, the present invention also provides a pure inorganic typical gel, which includes tightly assembled nanorod assemblies and a solution for dispersing the tightly assembled nanorod assemblies, wherein the nanorod assemblies contain inorganic one-dimensional nanorods and anions that can participate in the assembly of inorganic one-dimensional nanorods; and the inorganic one-dimensional nanorods contain at least rare earth metal elements.

[0031] Preferably, the anion concentration is greater than 10M.

[0032] In the seventh aspect, the present invention also provides a method for converting the pure inorganic stimuli-responsive sol into a pure inorganic typical gel, comprising adding anions that can participate in the assembly of nanorods into the pure inorganic stimuli-responsive sol until the dispersed inorganic one-dimensional nanorods in the pure inorganic stimuli-responsive sol are converted into tightly assembled nanorod assemblies.

[0033] In an eighth aspect, the present invention also provides a method for converting the pure inorganic thixotropic gel with adjustable physical properties into a pure inorganic typical gel in response to stimulation, wherein anions that can participate in the assembly of nanorods are added to the pure inorganic thixotropic gel with adjustable physical properties until the loosely assembled nanorod assemblies in the pure inorganic thixotropic gel are converted into tightly assembled nanorod assemblies.

[0034] In the ninth aspect, the present invention also provides a method for converting the pure inorganic typical gel into a thixotropic gel, comprising reducing the concentration of anions that can participate in the assembly of nanorods in the pure inorganic typical gel until the tightly assembled nanorod assemblies in the pure inorganic typical gel are converted into loosely assembled nanorod assemblies.

[0035] Preferably, the method of reducing the concentration of anions that can participate in the assembly of nanorods comprises adding chemical solutions, centrifugation, dialysis or ultrafiltration.

[0036] Preferably, when the anions that can participate in the assembly of the nanorods are hydroxide ions or carbonate ions, the chemical solution is one or more of hydrochloric acid, nitric acid, boric acid, citric acid, and acetic acid.

[0037] Preferably, the dialysis time is greater than 1 hour, and the ultrafiltration time is greater than 1 minute; The external solution used for dialysis is one or more of hydrochloric acid, nitric acid, boric acid, citric acid, and acetic acid.

[0038] In the tenth aspect, the present invention also provides a method for converting the pure inorganic typical gel into a pure inorganic stimulus-responsive sol, comprising reducing the concentration of anions that can participate in the assembly of nanorods in the pure inorganic typical gel until the tightly packed nanorod assemblies in the pure inorganic typical gel are converted into dispersed inorganic one-dimensional nanorods.

[0039] Preferably, the method of reducing the concentration of anions that can participate in the assembly of nanorods comprises adding chemical solutions, centrifugation, dialysis or ultrafiltration.

[0040] Preferably, when the anions that can participate in the assembly of the nanorods are hydroxide ions or carbonate ions, the chemical solution is one or more of hydrochloric acid, nitric acid, boric acid, citric acid, and acetic acid.

[0041] Preferably, the dialysis time is greater than 1 hour, and the ultrafiltration time is greater than 1 minute; The external solution used for dialysis is one or more of hydrochloric acid, nitric acid, boric acid, citric acid, and acetic acid.

[0042] In an eleventh aspect, the present invention further provides an application of a pure inorganic stimuli-responsive sol in sterilization, hemostatic materials, wound recovery materials, drug carriers, medical excipients, cosmetic materials or sunscreen products, which at least includes the steps of converting the pure inorganic stimuli-responsive sol into a pure inorganic thixotropic gel or a pure inorganic typical gel and / or converting the pure inorganic thixotropic gel or the pure inorganic typical gel into a pure inorganic stimuli-responsive sol; The pure inorganic stimuli-responsive sol comprises dispersed inorganic one-dimensional nanorods and a solution for dispersing the dispersed inorganic one-dimensional nanorods, wherein the inorganic one-dimensional nanorods contain at least a rare earth metal element.

[0043] In a twelfth aspect, the present invention further provides an application of a pure inorganic thixotropic gel with adjustable physical properties in sterilization, hemostatic materials, wound recovery materials, drug carriers, medical excipients, cosmetic materials or sunscreen products, which at least includes the steps of converting the pure inorganic thixotropic gel into a pure inorganic stimulus-responsive sol or a pure inorganic typical gel and / or converting the pure inorganic stimuli-responsive sol or a pure inorganic typical gel into a pure inorganic thixotropic gel; The pure inorganic thixotropic gel comprises loosely assembled nanorod assemblies and a solution for dispersing the loosely assembled nanorod assemblies; The loosely assembled nanorod assembly comprises inorganic one-dimensional nanorods and anions that can participate in the assembly of the inorganic one-dimensional nanorods; and the inorganic one-dimensional nanorods at least comprise rare earth metal elements.

[0044] In a thirteenth aspect, the present invention further provides an application of a pure inorganic typical gel in sterilization, hemostatic materials, wound recovery materials, drug carriers, medical excipients, cosmetic materials or sunscreen products, which at least includes the steps of converting the pure inorganic typical gel into a pure inorganic stimulus-responsive sol or a pure inorganic thixotropic gel and / or converting the pure inorganic stimulus-responsive sol or the pure inorganic thixotropic gel into a pure inorganic typical gel; The pure inorganic typical gel comprises tightly packed nanorod assemblies and a solution for dispersing the tightly packed nanorod assemblies; The tightly packed nanorod assembly comprises inorganic one-dimensional nanorods and anions that can participate in the assembly of the inorganic one-dimensional nanorods; and, The inorganic one-dimensional nanorods contain at least rare earth metal elements.

[0045] Therefore, the present invention has the following beneficial effects: (1) The present invention solves the problem of regulating the physical properties of inorganic nanogels by using inorganic nanorods that can be assembled by ions. First, compared with inorganic gel materials of other morphologies, inorganic one-dimensional nanorods undergo physical structural changes through self-assembly, have a better basis for regulating physical properties, and the intensity change amplitude can exceed 10,000 times. Secondly, inorganic one-dimensional nanorods do not need to add additional surface modification reagents, and can control the ion concentration to convert the dispersed inorganic one-dimensional nanorods into loosely assembled nanorod assemblies and tightly assembled nanorod assemblies in turn. In this process, in addition to requiring only cheap inorganic materials, there is also a qualitative change in convenience and cost in further processing and practical applications. Based on the characteristic of this material that physical property changes can be achieved without replacing ligands, this material has extremely high advantages in various applications.

[0046] (2) The present invention has successfully realized the preparation of thixotropic (structural self-recovery) inorganic gel materials, expanded the application field of inorganic materials, and successfully realized the formation of a structurally recoverable thixotropic gel structure by assembling inorganic one-dimensional nanorods.

[0047] (3) The method of the present invention is low in cost and easy to operate. The prepared thixotropic gel has both good thixotropic properties and good structural and physical property adjustability, and is a material that can be used in a comprehensive manner. By adjusting the type and concentration of ions, its physical properties can be changed to make it suitable for a variety of practical needs, such as liquid dressings for wounds, facial gel dressings for beauty, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 These are transmission electron microscope images of the cerium phosphate nanorod assembly in Example 1 at different magnifications.

[0049] Figure 2 The element distribution diagram, XRD diagram, XPS diagram and photograph of the cerium phosphate nanorod assembly in Test Example 1.

[0050] Figure 3 Transmission electron microscope images and photos of lanthanum phosphate, praseodymium phosphate, neodymium phosphate, samarium phosphate, europium phosphate, and gadolinium phosphate nanorod assemblies prepared using different precursors in Test Example 1.

[0051] Figure 4 3ITT results and thixotropy schematic diagram of the cerium phosphate nanorod assembly in Test Example 1.

[0052] Figure 5 These are transmission electron microscope images of the cerium phosphate nanorod assembly in Example 2 at different magnifications.

[0053] Figure 6 These are photos of thixotropic inorganic hydrogels of different concentrations in Example 2.

[0054] Figure 7 The transmission electron microscope image and 3ITT test results of the cerium phosphate nanorod assembly after dialysis in Test Example 2.

[0055] Figure 8 The transmission electron microscope images and 3ITT test results of the cerium phosphate nanorod assembly in Test Example 3 after adding different concentrations of phosphate ions again.

[0056] Fig. 9 This is a transmission electron microscope image of the cerium phosphate nanorod assembly after adding different ions in Test Example 4.

[0057] Fig.10 This is the element distribution diagram after sodium molybdate and sodium tungstate are added to the cerium phosphate nanorod assembly in Test Example 5.

[0058] Fig.11 This is a dark-field transmission electron micrograph of the cerium phosphate nanorod assembly in Example 3 undergoing four cycles of cyclic transformation between a thixotropic gel and a typical gel using sodium hydroxide and hydrochloric acid.

[0059] Fig.12 This is a rheological test diagram of the cerium phosphate nanorod assembly in Example 3 undergoing four cycles of transition between a thixotropic gel and a typical gel using sodium hydroxide and hydrochloric acid.

[0060] Fig.13 Schematic diagram of the transition of the cerium phosphate nanorod assembly among sol, thixotropic gel and typical gel in Example 3.

[0061] Fig.14 Photos of nanorod assemblies with different hydroxide concentrations.

[0062] Fig.15The transmission electron microscope images, photos, size statistics and 3ITT test results of nanorods of different sizes in Comparative Example 1 are shown.

[0063] Fig.16 This is the ultraviolet and visible light transmittance test of the cerium phosphate nanorod assemblies of different concentrations, different ion conditions, different sizes and compared with nanofibers in Example 4.

[0064] Fig.17 These are the test results of the antioxidant properties of the cerium phosphate nanorod assembly in Example 5 using the PTIO and ABTS methods.

[0065] Fig.18 These are the test results of the cerium phosphate nanorod assembly in Example 5 in promoting wound recovery in a full-thickness defect model in mice.

[0066] Fig.19 This is the SOD activity test result of the cerium phosphate nanorod assembly in Example 6 using a superoxide detection kit.

[0067] Fig. 20 These are photos of the intestines and the condition of mice in the DSS-induced mouse colitis model established by the cerium phosphate nanorod assembly in Example 6.

[0068] Fig.21 This is the detection of inflammatory factors in the DSS-induced colitis model of mice using the cerium phosphate nanorod assembly in Example 6.

[0069] Fig. 22 This is the test of the bactericidal performance of the cerium phosphate nanorod assembly in Example 7 against Candida albicans. DETAILED DESCRIPTION

[0070] The present invention is further described below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0071] Example 1 Weigh 0.951g of cerium acetate (molecular weight 317, 0.003mol) and add it to 10mL of deionized water, stir magnetically until dissolved. Take 0.5mL of commercially available concentrated phosphoric acid (85%) and add it to 10mL of deionized water, and take 0.35mL of ammonia water (28%) to mix. At room temperature, slowly add the latter to the former under vigorous stirring. After the reaction is completed, centrifuge the reactants and redisperse them in water, repeat twice to obtain a thixotropic inorganic hydrogel.

[0072] By replacing cerium acetate with an equal molar amount of cerium nitrate, praseodymium nitrate, promethium nitrate, samarium nitrate, europium nitrate, gadolinium nitrate and other nitrates, acetates and other raw materials, the corresponding metal phosphate nanorods can be prepared, which also have the above-mentioned properties.

[0073] Figure 1 are transmission electron microscope images of the cerium phosphate nanorod assembly at different magnifications in Example 1; Figure 1 It can be seen that what was prepared is an assembly of nanorods.

[0074] Figure 2 The element distribution diagram, XRD diagram, XPS diagram and photos of the cerium phosphate nanorods in Example 1 are shown in FIG. Figure 2 It can be seen that the prepared material is cerium phosphate.

[0075] Figure 3 Transmission electron microscope images and photos of nanorod assemblies prepared by replacing cerium nitrate with other metal nitrates in Example 1; Figure 3 It can be seen that these phosphate nanorods have similar properties.

[0076] Test Example 1 The thixotropic gel of cerium phosphate nanorods prepared in Example 1 was tested for its thixotropic properties by the three-stage thixotropic test (3ITT) method. The specific conditions are: 25, 50, 75 and 100 mg·mL-1 of phosphate nanorod self-assembly samples were prepared by dilution with deionized water, and 5 mL of each was taken as a thixotropic test sample. The thixotropic test was carried out using an MCR-302 rheometer, and the test process was divided into 4 cycles of three-stage thixotropic tests (3ITT). The sample was placed under a parallel plate with a diameter of 25 mm, the sample gap was 1.0 mm, the temperature was maintained at 25°C, and the angular frequency was 10 rad·s -1 The test procedure for a single cycle is as follows: 1. Fixed strain of 0.1% for 60 s. 2. Fixed strain of 100% for 30 s.

[0077] Depend on Figure 4 It can be seen that, in general, the higher the concentration of the cerium phosphate nanorod self-assembly, the higher the G' and G", indicating that its structural strength is positively correlated with the material concentration. In addition, under low strain shear force, G' is slightly higher than G", indicating that when the cerium phosphate nanorod self-assembly is at rest or under a small force, it exhibits gel properties; under high strain shear force, the height of G' and G" is reversed, and the cerium phosphate nanorod self-assembly exhibits sol properties, indicating that the gel structure of the cerium phosphate nanorod self-assembly can be destroyed under a larger force. When the high strain shear force is converted back to low strain shear force, the cerium phosphate nanorod self-assembly can restore its original strength in a very short time, indicating that it has a good ability to recover the structure, that is, thixotropy.

[0078] Example 2 Weigh 1.3g of cerium nitrate (molecular weight 434, 0.003mol) and add it to 10mL of deionized water, stirring magnetically until dissolved. Take 0.5mL of commercially available concentrated phosphoric acid (85%) and add it to 10mL of deionized water, and take 0.35mL of ammonia water (28%) to mix. At room temperature, slowly add the latter to the former under vigorous stirring. After the reaction is completed, centrifuge the reactants and redisperse them in water. Repeat twice to obtain a thixotropic inorganic hydrogel. Hydrogel samples of different concentrations can be obtained by centrifugal concentration.

[0079] Depend on Figure 5 It can be seen from TEM observation that the sample is an assembly of cerium phosphate nanorods.

[0080] Water (0 mg / mL) and 50, 100, 150, 200 mg / mL thixotropic inorganic hydrogels are shown in the photo. Figure 6 shown.

[0081] Test Example 2 The cerium phosphate nanorod thixotropic gel prepared in Example 2 was dialyzed in a hydrochloric acid solution to remove the ions involved in the assembly of the cerium phosphate nanorod self-assembly.

[0082] Depend on Figure 7 It can be seen that by observing the cerium phosphate self-assembly sample after dialysis through TEM, it can be found that the dendritic self-assembly structure is almost completely destroyed, leaving only some nanorods dispersed and piled. At the same time, by performing 3ITT test on the dialyzed sample, the results show that the dialyzed sample almost lost its thixotropy. The above results show that the fundamental reason for the self-assembly of nanorods is that ions in the environment participate in the assembly, and this dendritic assembly gives the cerium phosphate nanorods thixotropy.

[0083] Test Example 3 The sol product obtained in step 2 was tested by adding different concentrations of phosphate ions into the sol product.

[0084] Depend on Figure 8 It can be seen that as the concentration of phosphate ions in the environment increases, the degree of assembly of cerium phosphate nanorods also increases. At the same time, their 3ITT results also show the same trend. As the concentration of phosphate ions increases, the thixotropic properties of the material become closer to the sample before dialysis.

[0085] Test Example 4 The sol product obtained in Test Example 2 was added with ammonium chloride, ammonium nitrate, ammonium fluoride and sodium hydroxide solutions of the same concentration.

[0086] Depend on Fig. 9It can be seen that chloride ions have almost no effect on the assembly of nanorods, nitrate ions promote a weak assembly of nanorods, and fluoride ions and hydroxide ions lead to an assembly effect similar to that of high-valent anions. Except for chloride ions, which have extremely weak polarization effects, other anions basically have the effect of participating in the assembly.

[0087] Test Example 5 The sol product obtained in Test Example 2 was added with sodium molybdate and sodium tungstate solutions.

[0088] Depend on Fig.10 It can be seen that through element distribution analysis, it can be observed that the signals of tungstate ions, molybdate ions and cerium phosphate nanorods overlap, indicating that anions are involved in the assembly, resulting in changes in the dispersion of nanorods and thus changes in physical properties.

[0089] Example 3 The thixotropic gel of cerium phosphate nanorods in Example 1 was used to adjust the physical properties using sodium hydroxide and hydrochloric acid to transform the thixotropic gel into a typical gel. By increasing the hydroxide concentration by sodium hydroxide, the thixotropic gel can be transformed into a typical gel; by adding hydrochloric acid to remove the hydroxide, the thixotropic gel can be transformed again. The hydroxide concentration in the gel can be adjusted by hydrochloric acid and sodium hydroxide to 10 -15 -10M to present different gel states.

[0090] In order to explore the structural and physical property changes of the material, transmission electron microscopy and rheological testing methods were used.

[0091] Depend on Fig.11 It can be seen that in the four-cycle transformation, significant changes in the microstructure and orientation of the thixotropic gel and the typical gel can be observed. In the transformation from the thixotropic gel to the typical gel, the nanorods change from a stretched dendrite structure to an intertwined vine-like structure, and the assembled nanorods are almost completely aligned in the same direction, forming a strong three-dimensional structure.

[0092] Depend on Fig.12 It can be seen that there is no obvious attenuation in performance during the four rounds of cyclic transformation, indicating that the nanorod assembly has excellent reversible transformation ability between thixotropic gel and non-thixotropic gel.

[0093] Depend on Fig.13 It can be seen that by adjusting the ions, the nanorod assembly can be adjusted between three states: sol, thixotropic gel and typical gel.

[0094] Depend on Fig.14 It can be seen that the photos of nanorod assemblies with different hydroxide concentrations show different gel states, and the adjustment range can be 10 -15 -10M.

[0095] Comparative Example 1 Weigh 1.3g of cerium nitrate (molecular weight 434, 0.003mol) and add it to 10mL of deionized water, stir magnetically until dissolved. Take 0.5mL of commercial concentrated phosphoric acid (85%) and add it to 10mL of deionized water, and take 0.35mL of ammonia water (28%) and mix. At 40, 60, and 80 degrees Celsius, slowly add the latter to the former under vigorous stirring. After reacting for 24 hours, centrifuge the reactant and redisperse it in water, repeat twice to obtain thixotropic inorganic sol and gel.

[0096] Depend on Fig.15 It can be seen that the higher the reaction temperature, the larger the size of the nanorods, the lower the assembly degree, and the worse the thixotropic gel performance.

[0097] Example 4 The cerium phosphate nanorod assembly was prepared using the preparation method in Example 2 to test the visible light and ultraviolet light transmittance of the material.

[0098] Depend on Fig.16 It can be seen that with the increase of the concentration of cerium phosphate nanorods self-assembly, the transmittance of ultraviolet light and visible light continues to decrease. Even when the concentration increases to 10 mg mL -1 When the concentration of cerium phosphate nanorods is 0.1777 W / m, the cerium phosphate nanorod self-assembly still maintains a high level of transparency. Moreover, the nanorod assembly itself has no obvious effect on blocking light. At the same time, as the size of the nanorods increases, the transmittance in the visible light region decreases significantly, especially for the largest cerium phosphate nanorods synthesized at 80°C, whose visible light transmittance is similar to that of the smallest cerium phosphate nanorod self-assembly at 10 times the concentration. Nanofibers and cerium phosphate nanorod self-assemblies show huge differences in visible light absorptivity.

[0099] Example 5 The cerium phosphate nanorod assembly in Example 2 was used to explore wound recovery. By contacting the body fluid environment and adding hydrochloric acid, the material can form a typical gel, which can be used to cover the wound for wound recovery.

[0100] In order to explore the role of the material in promoting wound recovery, the ability of the material to scavenge reactive oxygen species was detected by using PTIO and ABTS.

[0101] Depend on Fig.17 It can be seen that the cerium phosphate nanorod assembly has the ability to scavenge active oxygen.

[0102] In order to explore the material's promoting effect on wound recovery, a mouse upper full-thickness cortical excision wound model was established. The cerium phosphate nanorod assembly formed a coating layer with body fluids at the wound site, and the wound recovery was observed to evaluate its ability to promote wound recovery.

[0103] Depend on Fig.18It can be seen that the cerium phosphate nanorod assembly has a good ability to promote wound recovery.

[0104] Example 6 The cerium phosphate nanorod assembly in Example 2 was used to explore the treatment of enteritis.

[0105] In order to explore the therapeutic effect of the material on enteritis, the SOD enzyme activity of the material was detected by using a superoxide detection kit.

[0106] Depend on Fig.19 It can be seen that cerium phosphate itself has SOD enzyme activity, and its clearance rate increases with the increase of concentration.

[0107] In order to explore the therapeutic effect of the material on enteritis, a mouse colitis model was established by DSS induction, and the cerium phosphate nanorod assembly was administered by oral gavage to observe the relief of intestinal inflammation. Blood and intestinal tissue were obtained after dissection, and inflammatory factors were detected to evaluate its anti-inflammatory ability.

[0108] Depend on Fig. 20 It can be seen that the cerium phosphate nanorod assembly can alleviate enteritis, without obvious shortening of the intestine and blood in the stool.

[0109] Depend on Fig.21 It can be seen that inflammatory factors were significantly reduced.

[0110] Example 7 The cerium phosphate nanorod assembly in Example 2 was used to explore the bactericidal performance. Candida albicans was cultured in the presence of the cerium phosphate nanorod assembly, and its bactericidal performance was tested by counting colonies on a plate.

[0111] Depend on Fig. 22 It can be seen that the nanorod assembly has bactericidal properties and can achieve a better bactericidal effect in a shorter time.

[0112] The specific embodiments described herein are merely examples of the spirit of the present invention. A person skilled in the art of the present invention may make various modifications or additions to the specific embodiments described or replace them in a similar manner, but this will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A pure inorganic thixotropic gel with adjustable physical properties, wherein the adjustable physical properties at least include adjustable physical state, strength, and microscopic morphology, characterized in that: The pure inorganic thixotropic gel comprises loosely assembled nanorod assemblies and a solution for dispersing the loosely assembled nanorod assemblies; The nanorod assembly comprises inorganic one-dimensional nanorods and anions that can participate in the assembly of the inorganic one-dimensional nanorods; and the inorganic one-dimensional nanorods at least comprise rare earth metal elements.

2. A pure inorganic thixotropic gel with adjustable physical properties according to claim 1, characterized in that: The inorganic one-dimensional nanorods are phosphates of rare earth metal elements.

3. A pure inorganic thixotropic gel with adjustable physical properties according to claim 1 or 2, characterized in that: The rare earth metal element is at least one of lanthanum, cerium, spectrium, promethium, samarium, europium and gadolinium.

4. A pure inorganic thixotropic gel with adjustable physical properties according to claim 1, characterized in that: The concentration of the inorganic one-dimensional nanorods in the pure inorganic sol is less than 200 mg / mL.

5. A pure inorganic thixotropic gel with adjustable physical properties according to claim 1, 2 or 4, characterized in that: The anions that can participate in the assembly of nanorods do not include chloride ions.

6. A pure inorganic thixotropic gel with adjustable physical properties according to claim 5, characterized in that: The anions that can participate in the assembly of nanorods include one or more of nitrate ions, phosphate ions, hydroxide ions, carbonate ions, molybdate ions, tungstate ions, titanate ions, sulfate ions, and bismuth ions.

7. A pure inorganic thixotropic gel with adjustable physical properties according to claim 1, characterized in that: The anion concentration is 10 -15 -10M.

8. A method for preparing a pure inorganic thixotropic gel with adjustable physical properties, characterized in that: The following steps are involved: A substance for reacting with the salt of the rare earth metal element to form an inorganic one-dimensional nanorod and an inducer are added to a solution containing a salt of the rare earth metal element under stirring conditions to form a uniform liquid, and at the same time, the inorganic one-dimensional nanorods are controlled to self-assemble to form a loosely assembled nanorod assembly, and the reaction obtains a pure inorganic thixotropic gel with adjustable physical properties as described in any one of claims 1 to 7.

9. The method according to claim 8, characterized in that The salt of the rare earth metal element contains any one anion or a combination of multiple anions selected from the group consisting of nitrate ion, phosphate ion, hydroxide ion, carbonate ion, molybdate ion, tungstate ion, titanate ion, sulfate ion and bismuth ion.

10. The method according to claim 8 or 9, characterized in that: The substance used for reacting with the salt of rare earth metal elements to form inorganic one-dimensional nanorods is phosphoric acid.

11. The method according to claim 8, characterized in that The inducing agent is an alkaline solution.

12. The method according to claim 11, characterized in that The alkaline solution is any one or more combinations of ammonia water, sodium hydroxide and potassium hydroxide.

13. The method according to claim 8, characterized in that The reaction temperature is 0-100°C.

14. A pure inorganic stimuli-responsive sol, characterized in that: The pure inorganic stimuli-responsive sol comprises dispersed inorganic one-dimensional nanorods and a solution for dispersing the dispersed inorganic one-dimensional nanorods, wherein the inorganic one-dimensional nanorods contain at least a rare earth metal element.

15. The pure inorganic stimuli-responsive sol according to claim 15, characterized in that: The anion concentration of the solution is less than 10 -15 M.

16. A method for converting a pure inorganic thixotropic gel with adjustable physical properties into a pure inorganic stimuli-responsive sol according to any one of claims 1 to 7, characterized in that: The concentration of anions that can participate in the assembly of nanorods is removed or reduced in the pure inorganic thixotropic gel with adjustable physical properties until the loosely assembled nanorod assemblies in the pure inorganic thixotropic gel are transformed into dispersed inorganic one-dimensional nanorods, thereby obtaining the pure inorganic stimuli-responsive sol.

17. The method according to claim 16, characterized in that Methods for removing or reducing the concentration of anions that can participate in nanorod assembly include adding chemical solutions, centrifugation, dialysis, or ultrafiltration.

18. The method according to claim 17, characterized in that When the anions that can participate in the assembly of the nanorods are hydroxide ions or carbonate ions, the chemical solution is one or more of hydrochloric acid, nitric acid, boric acid, citric acid, and acetic acid.

19. The method according to claim 17, characterized in that The dialysis time is greater than 1 hour, and the ultrafiltration time is greater than 1 minute; The external solution used for dialysis is one or more of hydrochloric acid, nitric acid, boric acid, citric acid, and acetic acid.

20. A method for converting the pure inorganic stimulus-responsive sol according to claim 14 or 15 into a thixotropic gel, characterized in that: Anions that can participate in the assembly of inorganic one-dimensional nanorods are added to the pure inorganic stimuli-responsive sol until the dispersed inorganic one-dimensional nanorods are transformed into loosely assembled nanorod assemblies.

21. A pure inorganic typical gel, characterized in that: The pure inorganic typical gel includes tightly assembled nanorod assemblies and a solution for dispersing the tightly assembled nanorod assemblies, wherein the nanorod assemblies contain inorganic one-dimensional nanorods and anions that can participate in the assembly of inorganic one-dimensional nanorods; and the inorganic one-dimensional nanorods contain at least rare earth metal elements.

22. The pure inorganic typical gel according to claim 21, characterized in that The anion concentration is greater than 10M.

23. A method for converting the pure inorganic stimulus-responsive sol according to claim 14 or 15 into a pure inorganic typical gel, characterized in that: Anions that can participate in the assembly of nanorods are added to the pure inorganic stimuli-responsive sol until the dispersed inorganic one-dimensional nanorods in the pure inorganic stimuli-responsive sol are transformed into tightly assembled nanorod assemblies.

24. A method for converting the pure inorganic thixotropic gel with adjustable physical properties as claimed in any one of claims 1 to 7 into a pure inorganic typical gel in response to stimulation, characterized in that: Anions that can participate in the assembly of nanorods are added to the pure inorganic thixotropic gel with adjustable physical properties until the loosely assembled nanorod assemblies in the pure inorganic thixotropic gel are transformed into tightly assembled nanorod assemblies.

25. A method for converting the pure inorganic typical gel according to claim 21 or 22 into a thixotropic gel, characterized in that: The concentration of anions that can participate in the assembly of nanorods is reduced in the pure inorganic typical gel until the tightly packed nanorod assemblies in the pure inorganic typical gel are transformed into loosely packed nanorod assemblies.

26. The method according to claim 25, characterized in that The method of reducing the concentration of anions that can participate in the assembly of nanorods includes adding chemical solutions, centrifugation, dialysis or ultrafiltration.

27. The method according to claim 26, characterized in that When the anions that can participate in the assembly of the nanorods are hydroxide ions or carbonate ions, the chemical solution is one or more of hydrochloric acid, nitric acid, boric acid, citric acid, and acetic acid.

28. The method according to claim 26, characterized in that The dialysis time is greater than 1 hour, and the ultrafiltration time is greater than 1 minute; The external solution used for dialysis is one or more of hydrochloric acid, nitric acid, boric acid, citric acid, and acetic acid.

29. A method for converting the pure inorganic typical gel according to claim 21 or 22 into a pure inorganic stimulus-responsive sol, characterized in that: The concentration of anions that can participate in the assembly of nanorods is reduced in the pure inorganic typical gel until the tightly packed nanorod assemblies in the pure inorganic typical gel are transformed into dispersed inorganic one-dimensional nanorods.

30. The method according to claim 29, characterized in that The method of reducing the concentration of anions that can participate in the assembly of nanorods includes adding chemical solutions, centrifugation, dialysis or ultrafiltration.

31. The method according to claim 30, characterized in that When the anions that can participate in the assembly of the nanorods are hydroxide ions or carbonate ions, the chemical solution is one or more of hydrochloric acid, nitric acid, boric acid, citric acid, and acetic acid.

32. The method according to claim 30, characterized in that The dialysis time is greater than 1 hour, and the ultrafiltration time is greater than 1 minute; The external solution used for dialysis is one or more of hydrochloric acid, nitric acid, boric acid, citric acid, and acetic acid.

33. Application of a pure inorganic stimuli-responsive sol in sterilization, hemostatic materials, wound healing materials, drug carriers, medical excipients, cosmetic materials or sunscreen products, characterized in that: The method comprises at least the steps of converting a pure inorganic stimuli-responsive sol into a pure inorganic thixotropic gel or a pure inorganic typical gel and / or converting a pure inorganic thixotropic gel or a pure inorganic typical gel into a pure inorganic stimuli-responsive sol; The pure inorganic stimuli-responsive sol comprises dispersed inorganic one-dimensional nanorods and a solution for dispersing the dispersed inorganic one-dimensional nanorods, wherein the inorganic one-dimensional nanorods contain at least a rare earth metal element.

34. Application of a pure inorganic thixotropic gel with adjustable physical properties in sterilization, hemostatic materials, wound recovery materials, drug carriers, medical excipients, cosmetic materials or sunscreen products, characterized in that: The method comprises at least the steps of converting a pure inorganic thixotropic gel into a pure inorganic stimuli-responsive sol or a pure inorganic typical gel and / or converting a pure inorganic stimuli-responsive sol or a pure inorganic typical gel into a pure inorganic thixotropic gel; The pure inorganic thixotropic gel comprises loosely assembled nanorod assemblies and a solution for dispersing the loosely assembled nanorod assemblies; The loosely assembled nanorod assembly comprises inorganic one-dimensional nanorods and anions that can participate in the assembly of the inorganic one-dimensional nanorods; and the inorganic one-dimensional nanorods at least comprise rare earth metal elements.

35. Application of a pure inorganic typical gel in sterilization, hemostatic material, wound recovery material, drug carrier, medical auxiliary material, cosmetic material or sunscreen product, characterized in that: The method comprises at least the steps of converting a pure inorganic typical gel into a pure inorganic stimulus-responsive sol or a pure inorganic thixotropic gel and / or converting a pure inorganic stimulus-responsive sol or a pure inorganic thixotropic gel into a pure inorganic typical gel; The pure inorganic typical gel comprises tightly packed nanorod assemblies and a solution for dispersing the tightly packed nanorod assemblies; The tightly packed nanorod assembly comprises inorganic one-dimensional nanorods and anions that can participate in the assembly of the inorganic one-dimensional nanorods; and, The inorganic one-dimensional nanorods contain at least rare earth metal elements.

Citation Information

Cited By

  • Application of gel with reversible structure in preparation of physical blood coagulation material

    CN119792617A

  • Dressing for repairing skin defect wound as well as preparation method and application of dressing

    CN121197479A